2014
DOI: 10.1097/nmd.0000000000000217
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Trauma, Parental Death, and Their Co-occurrence in Relation to Current Suicidality Risk in Adults

Abstract: Although previous studies have suggested that childhood trauma and parental death are strongly associated with suicidality in adulthood, it is still unclear how these factors interact within the same population. A total of 1396 adults were recruited through nationwide multistage probability sampling in South Korea. Subjects were evaluated through face-to-face interviews using the Suicidality Module of the Mini-International Neuropsychiatric Interview and the Early Trauma Inventory Self Report-Short Form. Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
(18 reference statements)
1
5
1
Order By: Relevance
“…This study found that CEPD was associated with adulthood suicidal ideation among the late adulthood group. This finding is partially consistent with previous studies reporting significant relationships between CEPD and mental health [9,15]. For example, a cohort study of French elderly showed that those who experienced parental loss or separation during childhood were more likely to report new-onset of generalized anxiety disorder than those who did not [15].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study found that CEPD was associated with adulthood suicidal ideation among the late adulthood group. This finding is partially consistent with previous studies reporting significant relationships between CEPD and mental health [9,15]. For example, a cohort study of French elderly showed that those who experienced parental loss or separation during childhood were more likely to report new-onset of generalized anxiety disorder than those who did not [15].…”
Section: Discussionsupporting
confidence: 91%
“…However, previous studies have reported inconsistent associations between CEPD and adulthood mental health. A study examining whether childhood trauma and parental death are associated with adulthood suicidal risk among 1396 adults in Korea showed that CEPD is not significantly related to current suicidality risk [9]. Another study in Korea showed that male adults who experienced maternal death before 10 years of age were more likely to report lifetime suicide attempts than those who did not experience maternal death [10].…”
Section: Introductionmentioning
confidence: 99%
“…Suicide risk in the elderly was associated with physical and sexual abuse (Draper et al, 2008;Sachs-Ericsson et al, 2013). Indeed, most studies that focused on this link looked at adult populations (Bruwer et al, 2014;Jeon et al, 2014;Norman et al, 2012;Perales et al, 2012;Rajalin, Hirvikoski, & Jokinen, 2013;Tunnard et al, 2014;Vares et al, 2016). In a nationally representative sample of 55,299 respondents in 21 countries, childhood adversities were associated with an increased risk of lifetime suicide attempts and ideation.…”
Section: Childhood Maltreatment Suicide Riskmentioning
confidence: 99%
“…However, most studies have not comprehensively adjusted for key confounders, including the co-occurrence of more than one type of maltreatment [17,19,21], since physical abuse, emotional abuse and emotional negligence frequently occur together [22]. Also, maltreatment has been typically considered a dichotomous measure, i.e., classifying subjects as maltreated or not [16,17,23]. As a result, it is not yet clear how the different levels and types of childhood trauma are associated to suicidal behavior.…”
Section: Introductionmentioning
confidence: 99%